Advertising Tax Revenue Strategy to Increase Makassar City Original Revenue - Amiruddin (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2022)
This study aims to find out how the strengths, weaknesses, opportunities, and threats of advertisement tax revenue are and how the strategy is carried out by the Makassar City Government in increasing advertisement tax revenues in Makassar City. This research was conducted at the Office of the Regional Tax and Retribution Management Agency of Makassar City. The key respondents of this research are the Head of Division, Subdivision, and staff of Regional II Revenue Management Division. The method of collecting data is through in-depth interviews with respondents and analysis data on advertisement tax receipts, inflation data, and Makassar City GDP. The research data was analyzed using SWOT analysis. The results of the study: 1) analysis of the taxation environment, consisting of a) Strengths b) Weaknesses c) Opportunities, and 2) Strategies to increase advertising tax revenue: a) Increasing human resources and efforts to eliminate the negative organizational culture; b) Improving tax collection management; c) Improving the implementation of the Regional Regulation on PDRD; d) Increasing support for facilities and infrastructure, and e) Law enforcement.